Improved production of thermo-alkali-tolerant fungal cellulolytic cocktail following Co-fermentation of sugarcane bagasse and secondary sewage sludge - Singh P.; Pal D.B.; Mohammad A.; Alshahrani M.Y.; Ahmad I.; Mishra P.K.; Yoon T.; Srivastava N. (My University, 2025)
Cellulases are important industrial enzymes which are being employed in diverse bio-processing for a number of commercial applications. Particularly, in context of viable biomass to biofuels production technology, high cost of cellulolytic enzymes is the main hindrance in which cost of substrate contributes the most. Selection of appropriate substrates may reduce the production cost of these enzymes, and consequently cost involved in the biofuels production process can be significantly reduced. Therefore, the objective of the present study is to improve the enzyme production using the combination of low-cost and renewable substrates which include sugarcane bagasse (SCB) and secondary sewage sludge (S3). Furthermore, cellulase production has been carried out under the co-fermentation wherein fungal strain Rhizopus Oryzae NS5 has been utilized. Under the solid-state fermentation (SSF), both the substrates with a ratio of 6:6 g (SCB: S3) exhibited maximum cellulase production in 72 h at pH 5.0 and temperature 37 °C. The maximum 17 U/gds FP, 163 BGL, and 227 U/gds EG have been achieved using this optimized ratio of both the substrates. Additionally, the crude cellulase showed temperature tolerance ability at 45 °C up to 150 min and pH tolerance capability at pH 8.0 for 150 min. The current findings may be utilized to produce crude cellulase enzyme using low-cost renewable wastes for effective bioconversion processing of lignocellulosic biomass to produce variety of biofuels. Graphical abstract: (Figure presented.) © The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature 2022.